Persepsi Wajib Pajak Terhadap Etika Penggelapan Pajak - Resza Dian Handayani; Rachmawati Meita Oktaviani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
This istudy iaims ito iexamine ithe ifactors ithat iinfluence ithe iperception iof iethics ion itax ievasion iin ithe iall iindividual itaxpayers iregistered iat ithe iSouth iSemarang iPrimary iTax iOffice ias imany ias i100 irespondents. iThe ivariables iused iin ithis istudy iare ithe iindependen ivariables, iThe idata iused iin ithis istudy iis ithe iprimary idata iby iusing iquestionnaires. iData ianalysis iin ithis iresearch iis iassisted iby iusing. iSPSS iprogram. iData ianalysis itechnique iused iis imultiple ilinear iregression. iThe iresult iof ithe iresearch ishows ithat isignificant iat ilevel i0,05. iThe iresults iof ithis istudy iindicate ithat ithere iis ino isignificant iinfluence ion ithe iprobability iof ifraud idetection ivariable ion ithe itaxpayer's iperception ivariable iregarding itax ievasion iethics, ithe iexistence iof ia isignificant ieffect iof ithe idiscrimination ivariable ion ithe itaxpayer's iperception ivariable iregarding itax ievasion iethics, ithe iexistence iof ia inegative iand isignificant iinfluence ion ithe itax iservice ivariable ion ithe ivariable. itaxpayers' iperceptions iof itax ievasion iethics. i Keywords: iTax ievasion, iDicrimination